Treatment of canine cranial cruciate ligament disease - Duerr, F. M.; Martin, K. W.; Rishniw, M.; Palmer, R. H.; Selmic, L. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
Objective: To describe veterinarians’ treatment recommendations and decision-making factors for dogs with cranial cruciate ligament disease (CCLD).Methods: An online survey of American College of Veterinary Surgeons (ACVS)-Diplomates (surgeon group) and primary care veterinarians (practitioner group) was performed. The survey included questions on treatment recommendations for common case scenarios (small or large breed dog with complete or partial CCLD), treatment decision factors, non-surgical treatment options, and actual treatment, if any, provided for a client-owned dog as well as one owned by their family or close friend.Results: The response rate was 42% for the surgeon group (n = 305/723) and four percent for the practitioner group (n = 1145/ 27,771). Extracapsular stabilization (ES) was the most common treatment recommendation for CCLD in small (9.1 kg) breed dogs amongst surgeons and practitioners. Tibial plateau levelling osteotomy (TPLO) was the most common treatment recommendation for CCLD in large (27.2 kg) breed dogs amongst both groups. The two most important treatment decision factors were dog size (78% of practitioners, 69% of surgeons) and activity level (63% of practitioners, 52% of surgeons). The most common treatment provided for a dog of their own or close relation in the surgeon group was TPLO (64%) followed by ES (15%), whereas in the practitioner group it was ES (38%) followed by TPLO (30%).Clinical significance: Extracapsular stabilization and TPLO are the most commonly employed surgical procedures in the surveyed population; dog size and activity level (but not age) are the major factors influencing treatment decisions.
Keywords: Cranial cruciate disease; tibial plateau levelling osteotomy; TPLO; extracapsular stabilization; online survey